2018
DOI: 10.1371/journal.pgen.1007242
|View full text |Cite
|
Sign up to set email alerts
|

Impaired proteoglycan glycosylation, elevated TGF-β signaling, and abnormal osteoblast differentiation as the basis for bone fragility in a mouse model for gerodermia osteodysplastica

Abstract: Gerodermia osteodysplastica (GO) is characterized by skin laxity and early-onset osteoporosis. GORAB, the responsible disease gene, encodes a small Golgi protein of poorly characterized function. To circumvent neonatal lethality of the GorabNull full knockout, Gorab was conditionally inactivated in mesenchymal progenitor cells (Prx1-cre), pre-osteoblasts (Runx2-cre), and late osteoblasts/osteocytes (Dmp1-cre), respectively. While in all three lines a reduction in trabecular bone density was evident, only Gorab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 61 publications
4
57
0
1
Order By: Relevance
“…Similarly, mutations in the trans-Golgi protein RAB6interacting golgin (GORAB), which functions in COPI-mediated traffic, cause the skin and bone disorder gerodermia osteodysplastica, likely as a consequence of disrupted matrix protein glycosylation (Hennies et al, 2008;Witkos et al, 2019). This not only affects matrix assembly, but is also important for controlling TGFβ (also known as TGFB1) signalling to prevent cell senescence (Chan et al, 2018). Mutations in Golgi RAB33B cause Smith-McCort syndrome (Dupuis et al, 2013), an osteochondrodysplasia.…”
Section: Skin Bone and Connective Tissue Disordersmentioning
confidence: 99%
“…Similarly, mutations in the trans-Golgi protein RAB6interacting golgin (GORAB), which functions in COPI-mediated traffic, cause the skin and bone disorder gerodermia osteodysplastica, likely as a consequence of disrupted matrix protein glycosylation (Hennies et al, 2008;Witkos et al, 2019). This not only affects matrix assembly, but is also important for controlling TGFβ (also known as TGFB1) signalling to prevent cell senescence (Chan et al, 2018). Mutations in Golgi RAB33B cause Smith-McCort syndrome (Dupuis et al, 2013), an osteochondrodysplasia.…”
Section: Skin Bone and Connective Tissue Disordersmentioning
confidence: 99%
“…However, for decorin, its non-proteoglycan form is always a minor component, even though there is also an increase related to age [88]. In cortical bone, the level of decorin glycanation decreases with age [90]. Finally, the decorin GAG length is reduced in the tendon fascicle of old mice [91].…”
Section: Slrp Gag Moieties: Fingerprints Of the Tissue Status And Actmentioning
confidence: 99%
“…Defective glycanation is correlated with pathological states, for instance in gerodermia osteodysplastica. In the organism model corresponding to this pathology characterized by the early onset of osteoporosis, decorin and biglycan are glycanated to a lesser extent, and it is suggested that this defect is involved in the abnormal gain of periosteum thickness [90]. Equine degenerative suspensory ligament desmitis (DSLD), which affects tendons, ligaments, and other connective tissues and resembles Ehlers-Danlos syndrome, correlates with the accumulation of decorin carrying abnormally glycosylated GAG chains [105].…”
Section: Slrp Gag Moieties: Fingerprints Of the Tissue Status And Actmentioning
confidence: 99%
“…The mechanism by which RAB-6.2 may regulate glycosylation is likely indirect, resulting from the role of RAB-6.2 in Golgi trafficking of client proteins and/or glycosylation enzymes like BUS-17 (Fisher and Ungar, 2016). Significantly, Golgi-related glycosylation defects are also linked to many inherited diseases, some of which affect the skin and bones, and mutations in RAB6-interacting proteins cause severe inherited diseases with strong skin defects such as gerodermia osteodysplastica and congenital disorders of glycosylation (CDG) in humans (Chan et al, 2018;Freeze and Ng, 2011;Hennies et al, 2008;Egerer et al, 2015;Wu et al, 2004;Sun et al, 2007).…”
Section: Rab-62 Is Necessary For M Nematophilum Infectionmentioning
confidence: 99%